Voting Hopes or Fears? : White Voters, Black Candidates, and Racial Politics in America. - Reeves, Keith (Oxford University Press, 1998)
Through experimental studies, this book provides fresh empirical evidence that the issue of race still pervades the consciousness of American society and prevents blacks from winning elections in districts where whites comprise a majority of the electorate.